IPTEKS PROSEDUR PENGHAPUSAN BMN OLEH KPKNL MANADO - Karambut, Andrew Malahasa; Lasewa, Reinaldi; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2018)
In order manifest procedure deletion State wealth , accountability management Goods State property , destruction State wealth , and deletion State wealth , necessary existence the implementation of an efficient, if efekt and take responsibility answer in Goods State Property. total State assets which are in condition broken will to be problem in BMN management but should reported on report Goods State- owned or Balance sheet . On party the user goods required take responsibility answer in take care of and make use of Goods State- owned with the best that includes age economical , period benefits , shrinkage and supervision should always in report every the period to party always manager goods namely KPKNL Manado. Value The presented in balance is asset still . By because that , necessary there is effective management on Goods State property to produce balance sheet that can reliable with facts that occur in the field. Elimination Goods State Ownership is the last process in management Goods State- owned.Keywords : Procedures, State Property, Deletion